2010
DOI: 10.1677/joe-10-0305
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide induced by a high-glucose concentration attenuates production of angiogenic growth factors in hypoxic mouse mesenchymal stem cells

Abstract: Previous reports have shown that the paracrine system may be an important mediator in bone-marrow-derived mesenchymal stem cell (MSC) therapy for ischemic diseases. Hyperglycemia and hypoxia have been associated with increased levels of reactive oxygen species; oxidative stress may therefore influence the paracrine effects of MSCs under hypoxic conditions in diabetic patients, although the mechanism underlying this effect remains unknown. Hypoxia-inducible factor 1a (HIF-1a) regulates the transcription of hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
(51 reference statements)
0
24
0
1
Order By: Relevance
“…In diabetic patients, oxidative stress may also influence the paracrine effects of MSCs under hypoxic conditions. In hypoxic MSCs, high glucose attenuates the production of angiogenic growth factors, including hypoxia-induced factor-1α, VEGF-A, and PDGF-B, by significantly increased intracellular superoxide levels in MSCs [76,77] . In addition, the migratory capacity of MSCs is also impaired.…”
Section: Stem Cells Under Diabetic Conditionsmentioning
confidence: 99%
“…In diabetic patients, oxidative stress may also influence the paracrine effects of MSCs under hypoxic conditions. In hypoxic MSCs, high glucose attenuates the production of angiogenic growth factors, including hypoxia-induced factor-1α, VEGF-A, and PDGF-B, by significantly increased intracellular superoxide levels in MSCs [76,77] . In addition, the migratory capacity of MSCs is also impaired.…”
Section: Stem Cells Under Diabetic Conditionsmentioning
confidence: 99%
“…Although low levels of ROS increase HIF-1a expression and promote cardiovascular differentiation, high levels of ROS may inhibit HIF-1a activity by inhibiting the binding of coactivator p300 to HIF-1a (36,37). Furthermore, diabetes increases ROS levels through hyperglycemia and decreases the expression and activity of HIF-1a (38,39). In the current study, ROS levels were significantly increased, whereas HIF-1a expression and the number of Wt1 + epicardial cells and EPDCs were decreased in the hearts of embryos of pregestational diabetic mice.…”
Section: Wt1mentioning
confidence: 99%
“…VEGF secretion in MSCs was enhanced by hypoxia in several studies, 372 and hypoxia has been shown both to induce expression of and increase the half-life of VEGF mRNA. 373 VEGF secretion has been shown to be attenuated in hypoxic cultures by the presence of high glucose concentrations, 345 which may explain why the observed effect here was not more pronounced.…”
Section: Discussionmentioning
confidence: 74%
“…MSCs have been previously reported to be more sensitive to oxygen deprivation in the face of concurrent nutrient deprivation. 344,345 We employed PCR arrays to screen for signaling pathways related to colony formation, which might be perturbed by hypoxia. We observed small but significant changes in several genes, some of which regulated glycolysis and IGF signaling, and many with interesting connections to regulation of Wnt /β-catenin signaling, which is critical for maintenance of stemness in adult and embryonic stem cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation